Mini Tinjauan Literatur Pemanfaatan Software CACL 3D Pro untuk Berpikir Komputasi Siswa - Ridho Ardiansyah Dalimunthe; Yahfizham Yahfizham (STIKes Ibnu Sina Ajibarang, 2025)
The utilization of Calc 3D Pro software in learning computational thinking among students has shown significant potential in improving the understanding of geometric and mathematical concepts. In this literature review, various studies are discussed that identify how the use of Calc 3D Pro can help students develop critical and analytical thinking skills through three-dimensional visualization. With the interactive features offered, students can more easily understand the relationship between mathematical objects and their applications in everyday life. In addition, research shows that the use of this software can also increase students' learning motivation and engagement in the learning process. This review highlights the urgency of integrating technology in the field of education to enhance the effectiveness and appeal of the learning process. The utilization of Calc 3D Pro software in learning computational thinking among students has shown significant potential in improving the understanding of geometric and mathematical concepts. In this literature review, various studies are discussed that identify how the use of Calc 3D Pro can help students develop critical and analytical thinking skills through three-dimensional visualization. With the interactive features offered, students can more easily understand the relationship between mathematical objects and their applications in everyday life. In addition, research shows that the use of this software can also increase students' learning motivation and engagement in the learning process. This review highlights the urgency of integrating technology in the field of education to enhance the effectiveness and appeal of the learning process.